PENGARUH MODEL PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN PEMAHAMAN KONSEP IPAS DAN GAYA BELAJAR DALAM PEMBELAJARAN ILMU PENDIDIKAN IPS SD PADA SISWA KELAS IV SDN 011 BUKIT GAJAH - Rani, Afriza Rahma; Rizal, Muhammad Syahrul; Nasrul, Nasrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of the Contextual Teaching and Learning (CTL) model on students’ conceptual understanding of integrated science and social studies (IPAS) and their learning styles in fourth-grade students at SDN 011 Bukit Gajah. This research employed a quantitative approach with a quasi-experimental method using a Pretest-Posttest Control Group Design. The sample consisted of 50 students divided into an experimental group and a control group selected through purposive sampling. Data were collected using multiple-choice tests to measure conceptual understanding and questionnaires to identify students’ learning styles. Data analysis was conducted using descriptive statistics and inferential analysis through an independent sample t-test with SPSS. The results showed that the CTL model had a positive and significant effect on students’ conceptual understanding of IPAS, indicated by a significance value of 0.000 < 0.05 and tcount > ttable. Furthermore, the CTL model also significantly influenced students’ learning styles. These findings indicate that contextual learning enhances student engagement, accommodates diverse learning styles, and facilitates meaningful understanding by connecting learning materials to real-life contexts.